2002
DOI: 10.1136/mp.55.4.262
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the MDV oncogenic regions in an MDV transformed lymphoblastoid cell line

Abstract: Aims: Lymphoblastoid cell lines derived from Marek's disease virus (MDV) induced tumours have served as models of MDV latency and transformation. They are stable and can be cultured with no detectable MDV genomic alterations upon repeated passaging. An MDV transformed lymphoblastoid T cell line (T9 cell line) has been reported to contain a disrupted MDV BamHI-H fragment and a Rous associated virus insertional activation of the c-myb protooncogene. In an attempt to define the respective participation of c-myb a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Several studies have shown the presence of multiple forms of the meq transcript (Jones et al, 1992;Le Rouzic et al, 2002). One of these transcripts, termed Meq-sp, was initially identified in the MD cell line, MKT-1 (Peng et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the presence of multiple forms of the meq transcript (Jones et al, 1992;Le Rouzic et al, 2002). One of these transcripts, termed Meq-sp, was initially identified in the MD cell line, MKT-1 (Peng et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The meq gene has been known to be polymorphic and several variants have been reported, including L-meq (Chang et al, 2002c). The presence of multiple spliced transcripts of meq has also been suggested in several studies (Jones et al, 1992;Peng & Shirazi, 1996;Le Rouzic et al, 2002). Nevertheless, the functions of Meq and its variants in the establishment of latency or transformation have not been elucidated clearly.…”
Section: Introductionmentioning
confidence: 99%
“…D, dermis; F, feather; FC, follicular cavity (Payne, 2004(Payne, ). al., 1973Handberg et al, 2001;Davidson and Borenshtain, 2003;Baigent et al, 2005 (Beasley et al, 1970;Addinger and Calnek, 1973 Calnek et al, 1984b;Baigent et al, 1998 (Shek et al, 1983;Calnek et al, 1984b (Cantello et al, 1994(Cantello et al, , 1997 (Cantello et al, 1994(Cantello et al, , 1997 (Kung et al, 2001 (Ichijo et al, 1981;Baigent and Davison, 1999;Le Rouzic, 2002 (Baigent et al, 1998;Burgess and Davison, 2002 (Rouse et al, 1973;Payne and Rennie, 1976 Davison, 1999, 2002), 림프세포의 형질 전환 요소인 Meq가 다량 발현된다 (Ross et al, 1997 et al, 1979;Delecluse and Hammerschmidt, 1993a et al, 1979;Delecluse and Hammerschmidit, 1993a;Deleculuse et al, 1993b BamHI-H gene (Cui et al, 1991 (Fynan et al, 1993).…”
mentioning
confidence: 99%